New insights into the intestinal barrier through “gut-organ” axes and a glimpse of the microgravity’s effects on intestinal barrier - Nie, Hong-Yun; Ge, Jun; Huang, Guo-Xing; Liu, Kai-Ge; Yue, Yuan; Li, Hao; Lin, Hai-Guan; Zhang, Tao; Yan, Hong-Feng; Xu, Bing-Xin; Sun, Hong-Wei; Yang, Jian-Wu; et al. (Frontiers in Physiology, 2024)
Gut serves as the largest interface between humans and the environment, playing a crucial role in nutrient absorption and protection against harmful substances. The intestinal barrier acts as the initial defense mechanism against non-specific infections, with its integrity directly impacting the homeostasis and health of the human body. The primary factor attributed to the impairment of the intestinal barrier in previous studies has always centered on the gastrointestinal tract itself. In recent years, the concept of the "gutorgan" axis has gained significant popularity, revealing a profound interconnection between the gut and other organs. It speculates that disruption of these axes plays a crucial role in the pathogenesis and progression of intestinal barrier damage. The evaluation of intestinal barrier function and detection of enterogenic endotoxins can serve as "detecting agents" for identifying early functional alterations in the heart, kidney, and liver, thereby facilitating timely intervention in the disorders. Simultaneously, consolidating intestinal barrier integrity may also present a potential therapeutic approach to attenuate damage in other organs. Studies have demonstrated that diverse signaling pathways and their corresponding key molecules are extensively involved in the pathophysiological regulation of the intestinal barrier. Aberrant activation of these signaling pathways and dysregulated expression of key molecules play a pivotal role in the process of intestinal barrier impairment. Microgravity, being the predominant characteristic of space, can potentially exert a significant influence on diverse intestinal barriers. We will discuss the interaction between the "gut-organ" axes and intestinal barrier damage, further elucidate the signaling pathways underlying intestinal barrier damage, and summarize alterations in various components of the intestinal barrier under microgravity. This review aims to offer a novel perspective for comprehending the etiology and molecular mechanisms of intestinal barrier injury as well as the prevention and management of intestinal barrier injury under microgravity environment.